Pulse Shape Processing to correct Pile up and Dead Time at High Count Rate by using Digital Spectroscopy Analyzer (DSA) - Hussein, Adil M. (Sulaimani Journal for Pure and Applied Sciences, 2007)
Rise time parameter in digital spectroscopy analyzer (DSA) is used to obtain a new method for pulse shape processing which is used to correct dead time and pile up at high count rate. When the pile up rejecter has been used the dead time did not eliminate so much, but as the new method has been used (rise time parameter) the dead time decreased to its half value. The effect of rise time on the spectrum such as the relationship between the rise time and each of width pulse shape, dead time, gauss ratio, peak to valley ratio and peak to Compton ratio ,have been studied .
Keywords: Gamma pulse shape processing; dead time and pile up optimization